Managing relational legacies: Lessons from British Columbia, Canada - Sofiane Baba; Emmanuel Raufflet (Administrative Sciences, 2014)
Issues related to company-community relations and the social license to operate have emerged as strategic business issues. This paper aims to contribute to the growing body of research on long-term company-community relations. An analysis of the relationship between Alcan (Aluminum of Canada, Montréal, Canada part of Rio Tinto since 2007) with the Cheslatta Carrier First Nation in the Kemano-Kitimat area of northern British Columbia, Canada, provides three contributions. The first is related to the notion of relational legacy, which refers to the sedimentation of unresolved issues that have the potential to impede the realization of corporate activities and the reproduction of low levels of social license to operate. The second concerns stakeholder management. While the literature suggests that stakeholders should be managed by companies according to the degree of salience, this analysis suggests that researchers and managers should consider the evolution of the environmental context in their analyses. Third, the analysis suggests that small or marginalized groups, depicted by the stakeholder management literature as dormant stakeholders, should not be underestimated.
Keywords: 350; stakeholders; relational legacy; community engagement; community relations; controversy; social license to operate; social acceptance; local communities; sustainability; Aboriginal